Design and experimental performance analysis of a DC motor–axial flux permanent magnet generator (M-G) system - Wiwit Indah Rahayu; Muhammad Ridhwan Sufandi; Hasan Hasan (Jurnal Pendidikan Informatika dan Sains, 2026)
Renewable energy systems require reliable electrical generators to convert mechanical energy into electrical energy through the principle of electromagnetic induction. Among various generator technologies, the axial flux permanent magnet generator (AFPMG) has attracted considerable attention because of its compact structure, high efficiency, high power density, and excellent performance at low rotational speeds, making it suitable for small- and medium-scale renewable energy applications. However, the electrical performance of AFPMGs is strongly influenced by their design parameters and operating conditions, requiring experimental evaluation under controlled conditions. This study aims to design, fabricate, and experimentally evaluate a DC motor-driven axial flux permanent magnet generator (AFPMG) system for electromechanical DC–AC energy conversion. A DC motor was employed as the prime mover to drive the AFPMG, while the effects of stator winding turns, winding wire diameter, and permanent magnet dimensions on generator performance were investigated experimentally. Performance evaluation was conducted by measuring the output voltage, current, rotational speed, generated power, and overall electromechanical conversion efficiency of the integrated motor–generator system. The developed motor–generator system successfully generated stable alternating current (AC) output under various operating conditions. The experimental results demonstrate that the generator performance is significantly affected by the stator winding configuration and magnetic field strength, with improvements in these parameters leading to higher output voltage and power generation capability. The findings provide valuable insights into the design and optimization of compact axial flux permanent magnet generators for renewable energy applications.